Treatment of neovascular age-related macular degeneration in patients with diabetes - Cummings, M (2008)
The number of patients with type 2 diabetes continues to rise; an anticipated 300 million people will be affected by 2025. The immense social and economic burden of the condition is exacerbated by the initial asymptomatic nature of type 2 diabetes, resulting in a high prevalence of micro-and macrovascular complications at presentation. Diabetic retinopathy, one of the potential microvascular complications associated with diabetes, and neovascular age-related macular degeneration (AMD) are the two most frequent retinal degenerative diseases, and are responsible for the majority of blindness due to retinal disease. Both conditions predominantly affect the central macula, and are associated with the presence of retinal edema and an aggressive inflammatory repair process that accelerates disease progression. The associated retinal edema and the inflammatory repair process are directly involved in the breakdown of the blood-retinal barrier (BRB). Yet, the underlying alterations to the BRB caused by the diseases are very different. The coexistence of the two conditions appears to be relatively uncommon, suggesting that diabetes may even protect patients from developing neovascular AMD. However, it is thought that the inflammatory repair responses associated with diabetic retinopathy and neovascular AMD may be cumulative and, in patients affected by both, could result in chronic diffuse cystoid edema. Treatment considerations in such patients should, therefore, include the role of retinal edema and the increased susceptibility of patients with diabetes to potential systemic side effects associated with agents administered repeatedly for neovascular AMD treatment.